2011
DOI: 10.1088/0953-8984/23/21/215004
|View full text |Cite
|
Sign up to set email alerts
|

The autocorrelation function for island areas on self-affine surfaces

Abstract: The spatial distribution of regions that lie above contours of constant height through a self-affine surface is studied as a function of the Hurst exponent H. If the surface represents a landscape, these regions correspond to islands. When the surface represents the height difference for contacting surfaces, the regions correspond to mechanical contacts in the common bearing area model. The autocorrelation function C(Δr) is defined as the probability that points separated by Δr are both within islands. The sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Self-affine rough surfaces with the desired Hurst exponent H, h′ rms , λ s , and λ L are generated using a Fourier-filtering algorithm described previously (44). Fourier components for each wavevector q → have a random phase and a normally distributed amplitude that depends on the magnitude q.…”
Section: Methodsmentioning
confidence: 99%
“…Self-affine rough surfaces with the desired Hurst exponent H, h′ rms , λ s , and λ L are generated using a Fourier-filtering algorithm described previously (44). Fourier components for each wavevector q → have a random phase and a normally distributed amplitude that depends on the magnitude q.…”
Section: Methodsmentioning
confidence: 99%
“…For most of these phenomena it is critical to accurately estimate the true contact area for given thermo-electro-mechanical loads and given roughness of contacting surfaces. It is now well known that a simple load bearing area model, relying on a geometrical overlap of two rough surfaces considerably overestimates the true contact area [46,60], and for equal contact areas, the former results in a much higher transmissivity in transport problems [15]. Existing analytical models, asperity-based [27,9,66,38,26,1], as well as Persson's model [50,52] with its adjusted version [49], rely on a few approximations and thus cannot provide very accurate results in terms of true contact area over a wide interval of loading conditions (for a detailed discussion and comparison see [37,12,44,73,75]).…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [5,6] it was also shown that the contact stress-stress correlation function (in wavevector space) ⟨σ(q)σ(−q)⟩ ∼ q −α , where in the overlap model α = 2+H (where H is the Hurst exponent), while including the long-range elastic coupling α = 1 + H.…”
Section: Introductionmentioning
confidence: 99%